Spindle cell lesions of the breast - Yanjun Hou; Zaibo Li (Elsevier, 2021)
Spindle cell lesions of the breast (BSCLs) are uncommon and encompass a wide spectrum of entities, ranging from benign reactive lesions to high-grade malignancies. The wide spectrum of differential diagnoses and significant overlap of clinicopathological features of BSCLs can cause diagnostic difficulties. An accurate diagnosis is crucial for guiding the clinical management. A BSCL can generally be classified as low grade/bland looking or high grade/malignant looking proliferations. Immunohistochemistry and/or other ancillary studies are usually necessary to differentiate morphologically challenging spindle cell lesion cases. This review focuses on the histological features and differential diagnoses of common spindle cell lesions of the breast.